A storm is brewing: Antecedents of disaster preparation in risk prone locations. (15th March 2021) - Oetzel, Jennifer; Oh, Chang Hoon
Abstract: Research Summary: Research emphasizes the value of disaster preparation and the importance of experience in doing so, yet most companies fail to prepare. The antecedents of preparation are poorly understood, in part, because experience by itself only partly explains the story. To address these concerns, we developed two unique surveys: one from an international survey in 18 disaster‐prone countries and another from a U.S. survey in New York City and Miami. We find that organizational experience with natural disasters increases preparedness for future hazards. Also, organizational learning from other businesses and organiztions positively mediates this relationship. Managers are more willing to learn from others in locations characterized by high‐impact, low‐frequency disasters. In areas with low impact, high frequency disasters, managers more likely misjudge the severity of natural disasters. Managerial Summary: Despite the increasing frequency and severity of floods, storms, wildfires and other natural hazards, why do some firms in disaster‐prone areas prepare while others do not? To investigate, we conducted two studies: an international survey in 18 disaster‐prone countries and a U.S. survey in New York City and Miami. In both surveys, managers are more likely to prepare when their companies experienced prior disasters. Managers operating in locations characterized by high‐impact, low‐frequency disasters are more willing to learn from others. In contrast, managers in areas characterized by low impact, high frequency disasters, are more likely to prepare alone. Since effective disaster preparation typically entails working with, and learning from others, those companies that choose a go‐it‐alone strategy may misjudge disaster risk.